PENERAPAN HUKUMAN TINDAKAN KEBIRI KIMIA DALAM PERSPEKTIF HAK ASASI MANUSIA - Hutapea, Messy Rachel Mariana (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
Children are still victims of sexual violence by perpetrators who are stronger than victims. Children who are victims of sexual violence have a negative impact on the psychic and mental, so that children will have trauma that is difficult to be eliminated or even prolonged trauma. So that the government established the Law Number 17 of 2016 concerning the Establishment of the Government Regulation in Lieu of Law Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection into Law. In the laws and regulations, it has been regulated regarding the castration penalty of chemistry. Indonesia is a country that still upholds all human rights possessed by every community in Indonesia without discrimination. This chemical castration execution raises the pros and cons in people's lives. So this chemical castration is considered to have violated the Human Rights of perpetrators of sexual violence against children. This research wants to dig deeper about the use of chemical castration punishment in perpetrators of recurrent crimes in the human rights perspective. This study uses normative research methods with conceptual and legislative approaches. Chemical castration has not been one of the effective penalties and provides a deterrent for perpetrators of sexual violence, so the laws governing chemical castration punishment need to be reviewed.Anak masih menjadi korban kekerasan seksual yang dilakukan oleh para pelaku yang lebih kuat dari korban. Anak yang menjadi korban kekerasan seksual mendapatkan dampak yang negatif terhadap psikis dan batinnya, sehingga anak akan memiliki trauma yang susah untuk dihilangkan atau bahkan trauma tersebut berkepanjangan. Sehingga pemerintah membentuk peraturan Undang-Undang Nomor 17 tahun 2016 tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang Nomor 1 tahun 2016 tentang Perubahan Kedua atas Undang-undang Nomor 23 tahun 2002 tentang Perlindungan Anak menjadi Undang-Undang. Didalam peraturan perundang-undangan tersebut, telah diatur tentang hukuman kebiri kimia. Indonesia adalah negara yang masih menjunjung setiap Hak Asasi Manusia yang dimiliki oleh setiap masyarakat di Indonesia tanpa adanya diskriminasi. Eksekusi kebiri kimia ini menimbulkan pro dan kontra didalam kehidupan masyarakat. Sehingga kebiri kimia ini dianggap telah melanggar Hak Asasi Manusia dari pelaku kekerasan seksual terhadap anak. Penelitian ini ingin menggali lebih dalam tentang penggunaan hukuman kebiri kimia pada pelaku kejahatan berulang dalam persektif hak asasi manusia. Penelitian ini menggunakan metode penelitian normative dengan endekatan konseptual dan perundang-undangan. Kebiri kimia belum menjadi salah satu hukuman yang efektif dan membuat jera untuk pelaku kekerasan seksual, Sehingga undang-undang yang mengatur tentang hukuman kebiri kimia perlu dikaji ulang.